बलम्वु क्षेत्रका लिच्छवीकालिन शिलालेखहरुको वर्तमान अवस्था The Contemporary State of the Lichhavi Inscriptions of Balmbu - Shrestha, Sagar (Nepalese Culture, 2023)
This article is based on the present situation of stone inscription at ward no. 12 Chandragiri Municipality of Balambu area as referenced in the title. The article seeks to discuss the past and present situation of nine different stone inscriptions found at Balambu area. These inscriptions are valuable sources for the writing of Nepali’s history. These inscriptions were issued by various kings such as Basanta Deva, Kramalil, Ravi Gupta, Bhauma Gupta, Amsu Varma, Gana Deva, Bhimarjuna Deva, Jishnu Gupta, Narendra Deva, Shiva Deva II play an important role to write the history of Nepal. This research is a qualitative and comparative study of the differences in the physical condition of these inscriptions that were looked into and researched fifty years ago. These inscriptions which are witnesses of Nepalese long history has not caught the attention of the related institutions. Thus, the main objective of this research is to look into the physical condition of these inscriptions at various places of the ward no 12, Balambu area Chandragiri municipality. What was the physical condition of these inscriptions fifty years ago? In what ways are they different? How many have been lost? What is there physical condition at present? This research article seeks to unfold the how and why of these present conditions of these inscription. The Department of Archaeology the local municipality and community are the major stakeholder for the conservation and preservation of the cultural heritages. This article also investigates about: Who is responsible for the conservation of these Ancient inscriptions which belong to the Lichhavi period considered to be the golden era of Nepali history. Loss and damage of the inscription create problems for verification or correction against previous researches. This research will facilitate students, researchers and others to gather information about the status and present conditions of these stone inscription.